1991
DOI: 10.1083/jcb.115.4.1077
|View full text |Cite
|
Sign up to set email alerts
|

Connexin46, a novel lens gap junction protein, induces voltage-gated currents in nonjunctional plasma membrane of Xenopus oocytes.

Abstract: . Gap junctions are composed of a family of structural proteins called connexins, which oligomerize into intercellular channels and function to exchange low molecular weight metabolites and ions between adjacent cells . We have cloned a new member of the connexin family from lens cDNA, with a predicted molecular mass of 46 kD, called rat connexin46 (Cx46) . Since a full-length cDNA corresponding to the 2.8-kb mRNA was not obtained, the stop codon and surrounding sequences were confirmed from rat genomic DNA . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
422
0
4

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(440 citation statements)
references
References 49 publications
(69 reference statements)
14
422
0
4
Order By: Relevance
“…RT-PCR products of the appropriate size for all three connexins were amplified from the lens RNA, but only Cx43 was amplified from the liver RNA. This result is consistent with previous observations from mammals and birds that the Cx46 and Cx50 subfamilies are predominantly expressed in the lens (Paul et al, 1991;White et al, 1992;Rup et al, 1993;Jiang et al, 1994), whereas Cx43 is expressed in a variety of tissues, including the vascular system . RT-PCR analysis of adult lens RNA with primers specific for Cx43.4 (Essner et al, 1996), Cx35 (McLachlan et al, 2003, and Cx45.6 (Christie et al, manuscript in preparation) failed to detect expression (data not shown).…”
Section: Mouse and Chickensupporting
confidence: 93%
See 1 more Smart Citation
“…RT-PCR products of the appropriate size for all three connexins were amplified from the lens RNA, but only Cx43 was amplified from the liver RNA. This result is consistent with previous observations from mammals and birds that the Cx46 and Cx50 subfamilies are predominantly expressed in the lens (Paul et al, 1991;White et al, 1992;Rup et al, 1993;Jiang et al, 1994), whereas Cx43 is expressed in a variety of tissues, including the vascular system . RT-PCR analysis of adult lens RNA with primers specific for Cx43.4 (Essner et al, 1996), Cx35 (McLachlan et al, 2003, and Cx45.6 (Christie et al, manuscript in preparation) failed to detect expression (data not shown).…”
Section: Mouse and Chickensupporting
confidence: 93%
“…The expression of three different connexins has been detected in the mammalian lens. Cx46 and Cx50 are mainly expressed in the lens fiber cells (Paul et al, 1991;White et al, 1992), whereas Cx43 is restricted to the anterior lens epithelium (Yancey et al, 1992). The chicken orthologues of these connexins have been identified as Cx56, Cx45.6, and Cx43 (Musil et al, 1990;Rup et al, 1993;Jiang et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Cx46 was obtained from Dr. D. Paul [3]. Cx32E 1 43 [4] in the vector pGEM3Z (Pomega) was cut with BamHI and PmlI.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, there was no change in the current flowing into the extracellular space, and the hemichannels were closed before opening to form a cell-cell channel. When expression of Cx46 in Xenopus oocytes was found to be fatal and to cause a large non-specific increase in membrane conductance in low Ca 2+ conditions, it seemed to be a rule that proved the exception: opening of (non-junctional) hemichannels is bad for cells, and something unusual about Cx46 expressed in oocytes allows hemichannel opening unless relatively high Ca 2+ concentrations are added to prevent it [8,9]. …”
mentioning
confidence: 99%